THE ROLE OF WATER ELEMENTS IN FILM ART DIRECTING - Bintang B. Doeana; Diana Dewi (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
Water is a basic need for the survival of all creatures including all human beings, and water is also very influential in the order and pattern of people's life. In films, the appearance of water can relate to the elements of artistic planning, namely sets, make-up, properties and effects that make the aesthetics of the appearance of works of art to support the story and atmosphere that will be displayed, both positive and negative. The existence of elements of art directing in water is presented creatively and aesthetically in the field of film art directing. This research will discuss Water which can be described in the 'look and mood' of the story that will be displayed. And the purpose of this research is that filmmakers can use water as a medium in telling stories. This research method is descriptive qualitative accompanied by literature study, so that filmmakers can take advantage of aspects of art directing to produce good films. It is hoped that the results of the research will become input for filmmakers in the use of water through visual arrangement by paying attention to the elements of art directing according to the theme displayed.